Efficacies of continuous renal replacement therapy for severe patients with chronic renal failure and the influencing factors of long-term prognosis - Ma Qin-qin; Zhou Ying; Zhang Yan-nan; Chen Chen; Yu Ying-hua; Li Tian-min (Linchuang shenzangbing zazhi)
ObjectiveTo explore the clinical efficacy of continuous renal replacement therapy （CRRT） for severe patients with chronic renal failure （CRF） and examine the influencing factors of long-term prognosis.MethodsFrom September 2018 to April 2021， 160 hospitalized severe CRF patients were selected as research subjects. According to treatment options， observation group received CRRT （n=120） while control group had hemodialysis （n=40）. Both groups were treated conventionally after enrollment. Renal function parameters ［β2-microglobulin （β2-MG）， serum creatinine （Scr） & blood urea nitrogen （BUN）］ and the levels of microinflammatory factors ［interleukin-1/6 （IL-1/6） & tumor necrosis factor-alpha （TNF-α）］ were compared between two groups before and after treatment. IL-6， TNF-α， high-sensitivity C-reactive protein （hs-CRP）， parathyroid hormone （PTH）， homocysteine （Hcy）， uric acid， blood phosphorus and the incidence of adverse reactions after treatment all declined. Multivariate Logistic regression analysis was performed for the influencing factors of long-term prognosis of CRF patients on CRRT. A nomogram prediction model was constructed and receiver operating characteristic （ROC） curve and GiVITI calibration curve with a nomogram model were utilized for discrimination and calibration evaluations.ResultsPrior to treatment， no significant inter-group differences existed in the levels of β2-MG， Scr， BUN， IL-1， IL-6， TNF-α， hs-CRP， Hcy， PTH， blood phosphorus or uric acid （P>0.05）. After treatment， the levels of β2-MG， Scr and BUN were lower in observation group than those in control group. And the levels of β2-MG， Scr and BUN dropped in two groups than pre-treatment； the levels of IL-1， IL-6， BUN， TNF-α， hs-CRP， Hcy， PTH， blood phosphorus and uric acid were lower in observation group than those in control group； the incidence of adverse reactions was significantly lower in observation group than that in control group and the difference was statistically significant （P<0.05）. Multivariate Logistic regression analysis indicated that hypertension， heart failure and maintenance of hemodialysis time≥1 year were risk factors for long-term prognosis of CRRT. Serum albumin level≥30 g/L was a protective factor for long-term prognosis of CRRT. Nomogram model， degree of discrimination and degree of calibration all yielded excellent results.ConclusionCRRT has significant clinical efficacies in severe CRF patients. And hypertension， the long-term prognosis of CRF patients is worse for those with heart failure and complications of maintaining hemodialysis for more than 1 year .